On Males, Antioxidants and Infertility (MOXI): Certitudes, Uncertainties and Trends - Manuel Alfaro Gómez; María del Rocío Fernández-Santos; Alejandro Jurado-Campos; Pedro Javier Soria-Meneses; Vidal Montoro Angulo; Ana Josefa Soler; José Julián Garde; Virginia Rodríguez-Robledo (MDPI AG, 2023)
Male infertility (MI) involves various endogenous and exogenous facts. These include oxidative stress (OS), which is known to alter several physiological pathways and it is estimated to be present at high levels in up to 80% of infertile men. That is why since the late 20th century, the relationship between OS and MI has been widely studied. New terms have emerged, such as Male Oxidative Stress Infertility (MOSI), which is proposed as a new category to define infertile men with high OS levels. Another important term is MOXI: Male, Antioxidants, and Infertility. This term refers to the hypothesis that antioxidants could improve male fertility without the use of assisted reproductive technology. However, there are no evidence-based antioxidant treatments that directly improve seminal parameters or birth ratio. In this regard, there is controversy about their use. While certain scientists argue against their use due to the lack of results, others support this use because of their safety profile and low price. Some uncertainties related to the use of antioxidants for treating MI are their questionable efficacy or the difficulties in knowing their correct dosage. In addition, the lack of quality methods for OS detection can lead to excessive antioxidant supplementation, resulting in "reductive stress". Another important problem is that, although the inflammatory process is interdependent and closely linked to OS, it is usually ignored. To solve these uncertainties, new trends have recently emerged. These include the use of molecules with anti-inflammatory and antioxidant potential, which are also able to specifically target the reproductive tissue; as well as the use of new methods that allow for reliable quantification of OS and a quality diagnosis. This review aims to elucidate the main uncertainties about MOXI and to outline the latest trends in research to develop effective therapies with clinically relevant outcomes.